Development and evaluation of the organization`s logistics strategy based on the application of bifurcation theory - M. Yu. Uchirova; L. A. Ilin; S. V. Khudyakov (Вестник университета)
The article considers the main approaches to the development and evaluation of the organization’s logistics strategy based on the application of bifurcation theory. The paper notes that the greatest competitive advantages in the process of carrying out activities can be obtained by the company when designing a unique logistics strategy based on the individual features of the organization’s logistics system. The authors reveal that the bifurcation theory allows you to determine the conditionality of a qualitative dynamic change in the behavior of a logistics system by an infinitesimal change in certain parameters of the system. As part of the assessment of the organization’s logistics management strategy, bifurcation theory forms the basis for determining shift in the qualitative parameter of the system and makes it possible to assess the effect of this parameter on the behavior of the entire system as a whole and each functional subsystem separately. The study reflects that it is possible to determine the critical values of individual variables, when overcoming which the logistics system itself goes into unstable state. The main concept defining the process of critical transition of the state of the logistic system is the bifurcation point.